The Effect of Vitamin D Supplementation in Pregnant Woman for Pre-eclampsia Incidency : A Literature Review - Tia Mella Citra; Ratih Pramuningtyas; Tri Agustina; Erna Herawati; Ayu Mayangsari; Zhela Fatin Fatiha; Aulia Nissa Rizky Hariyono (Journal Research of Social Science, Economics, and Management, 2022)
Pre-eclampsia was defined as hypertension after 20 weeks of gestation with evidence of maternal organ dysfunction,uteroplacental, or proteinuria. Maternal vitamin D deficiency may be with an increased risk of pre-eclampsia. Nonetheless, To assess the impact of vitamin D supplementation on the risk of pre-eclampsia, we performed a literature review. We researched Google Scholar; PubMed; Research Gate; and Science Directs using keyword (“Vitamin D” OR “Hydroxyvitamin D (25(OH)D)”OR “25(OH)D” OR “25hydroxycholecalciferol”) AND (“Pregnancy” OR “Pregnant women” OR “Gestation”) AND (“Clinical trial” OR “Clinical study” OR “study” OR “prospective study” OR “Randomized controlled trial” OR “RCT”) from January 2006 – May 2021. A total 4 of 19.431 articles recorded at the identification stage by the criteria for inclusion. The articles are randomized controlled trial (RCT). A total of 329 pregnant woman are given various vitamin D supplements with dose range 400 - 4.000 IU. Some article combine with other vitamin (Calcium, Vitamin C+E) with a certain duration. Maternal ages range 20 years - 40 years with an gestational age 6 to more than 32 weeks. Vitamin D can reduce the risk of pre-eclampsia in pregnant women.